Evaluating Drainmod‐s to Predict Drainage Water Salinity and Groundwater Table Depth During Winter Cropping in Heavy‐Textured Paddy Soils†. (7th April 2019) - Davoodi, Kolsom; Darzi‐Naftchali, Abdullah; Aghajani‐Mazandarani, Ghasem
Abstract: Simulation models can quickly and cost‐effectively describe various aspects of management practices in newly reclaimed agricultural soils. In this research, the capability of the DRAINMOD‐S model was evaluated to predict the salinity of the subsurface drainage effluents in a newly subsurface drained paddy field during winter cropping. Measurements of groundwater table depths and drainage water salinity were taken in three conventional subsurface drainage systems at the Sari Agricultural Sciences and Natural Resources University, northern Iran, during three canola growing seasons (2011–2012, 2015–2016 and 2016–2017). The data were used to calibrate and validate the model. The model provided better predictions of groundwater table depths in shallower drainage systems. Measured and simulated drainage water salinities varied, respectively, from 620 to 1580 and 790–1430 mg l −1 in the calibration process and from 441 to 1640 and 656–1820 mg l −1 in the validation process. The differences between measured and simulated salt loads were in the range of 59–174 and 43–586 kg ha −1 in calibration and validation, respectively. The results indicated that DRAINMOD‐S can be used as a management tool to diminish environmental issues in heavy paddy soils from the viewpoint of salt load. © 2019 John Wiley & Sons, Ltd. Résumé: Les modèles de simulation peuvent décrire rapidement et de manière rentable divers aspects des pratiques de gestion dans les sols agricoles récemment régénérés. Dans cette recherche, la capacité du modèle DRAINMOD‐S a été évaluée pour prédire la salinité des effluents de drainage souterrains dans une rizière nouvellement drainée sous la surface lors de cultures hivernales. Les profondeurs de la nappe phréatique et la salinité de l'eau de drainage ont été mesurées dans trois systèmes de drainage souterrains classiques de l'Université des sciences agricoles et des ressources naturelles de Sari, au nord de l'Iran, au cours de trois saisons de culture du canola (2011–2012, 2015–2016 et 2016–2017). Les données ont été utilisées pour calibrer et valider le modèle. Le modèle fournit de meilleures prévisions des profondeurs de la nappe phréatique dans les systèmes de drainage moins profonds. La salinité mesurée et simulée de l'eau de drainage variait respectivement de 620–1580 et 790–1430 mg l −1 dans le processus d'étalonnage et de 441–1640 et 656–1820 mg l −1 dans le processus de validation. Les différences entre les charges de sel mesurées et simulées se situaient dans les limites de 59 à 174 et de 43 à 586 kg ha −1 lors de l'étalonnage et de la validation, respectivement. Les résultats ont montré que DRAINMOD‐S peut être utilisé comme un outil de gestion permettant de réduire les problèmes environnementaux dans les sols de paddy à texture épaisse du point de vue de la charge en sel. © 2019 John Wiley & Sons, Ltd.